Controlling the Emotional Bias: Performance, Late Positive Potentials, and the Effect of Anodal Transcranial Direct Current Stimulation (tDCS) - Faehling, Florian; Plewnia, Christian (Frontiers in Cellular Neuroscience, 2016)
Cognitive control of emotional processing is essential for adaptive human behavior. Biased attention towards emotionally salient information is critically linked with affective disorders and is discussed as a promising treatment target. Anodal (activity enhancing) transcranial direct current stimulation (tDCS) has been shown to increase healthy and impaired cognitive control over emotional distraction and is therefore widely used for the investigation and experimental treatment of this disorder. In this study, event-related potential (ERP) were recorded parallel to tDCS to track its online effects. Healthy volunteers (n=87) performed a delayed working memory paradigm with emotional salient and neutral distractors during stimulation with different intensities (sham, 0.5, 1, 1.5 mA). Measuring the late positive potential (LPP), an ERP that indexes attention allocation, we found that a valence-specific increase of the early portion of the LPP (eLPP, 250-500 ms) was associated with less emotional distraction in the sham group. Of note, stimulation with tDCS exerted an intensity related effect on this correlation. The later part of the LPP (lLPP, 500-1000 ms) was found to be correlated with reaction time, regardless of valence. General effect of tDCS on LPPs and task performance were not observed. These findings demonstrate that ERP recordings parallel to tDCS are feasible to investigate the neuronal underpinnings of stimulation effects on executive functions. Furthermore, they support the notion that the LPP induced by a distractive stimulus during a working memory task mirrors the additional allocation of neuronal resources with a specific sensitivity of the early LPP for highly arousing negative stimuli. Finally, together with the variable magnitude and direction of the emotional bias, the lack of systematic modulations of LPPs and behavior by tDCS further underlines the important influence of the individual brain activity patterns on stimulation effects both on the behavioral and neurophysiological level.